2020
DOI: 10.1016/j.jbo.2020.100313
|View full text |Cite
|
Sign up to set email alerts
|

The minimally invasive endoscopic technique for the treatment of symptomatic benign bone lesions: Preliminary results from a retrospective study

Abstract: Highlights Symptomatic benign bone lesions may cause pain and refractory limp. Conventional open surgery usually involves high risks of complications, which may greatly compromise the overall efficacy of surgery in the long term. This single-institution retrospective study of 34 patients with symptomatic benign bone lesions. All surgical procedures were performed under endoscopic guidance for direct visualization followed by complete curettage of tumor tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Benign spinal lesions include aneurysmal bone cysts, osteoid osteomas, and fibrous dysplasia, which tend to occur in the thoracic and lumbar spine. The incidence is low, accounting for approximately 1% of primary bone tumors [1,2]. They are usually found incidentally during physical examination, but local pain, nerve compression, and spinal deformity may also occur as the disease progresses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Benign spinal lesions include aneurysmal bone cysts, osteoid osteomas, and fibrous dysplasia, which tend to occur in the thoracic and lumbar spine. The incidence is low, accounting for approximately 1% of primary bone tumors [1,2]. They are usually found incidentally during physical examination, but local pain, nerve compression, and spinal deformity may also occur as the disease progresses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous osteoplasty (POP) is a procedure similar to PVP in principle and used for the treatment of bone lesions that can be accessed using puncture needles (4). Studies have shown that minimally invasive percutaneous imaging-guided techniques are safe and effective for the treatment of symptomatic, benign osteopathy (8)(9)(10). However, the clinical effectiveness of the treatment of cementoplasty still remains unclear.…”
Section: Introductionmentioning
confidence: 99%